2003
DOI: 10.1074/jbc.m300677200
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Pro-apoptotic Genegadd153/chop Is Elevated in Liver with Aging and Sensitizes Cells to Oxidant Injury

Abstract: Aging is generally accompanied by reduced tolerance to oxidative stress and altered responsiveness to proliferative signals. We have shown that hepatocytes derived from aged rats (24 -26 months) exhibit greater sensitivity to H 2 O 2 treatment and reduced proliferation following epidermal growth factor (EGF) treatment than cells of young adult rats (5-6 months). Here we examined the effects of aging and calorie restriction (CR) on expression of the oxidative stress-inducible and pro-apoptotic gene gadd153 (cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 44 publications
3
42
2
Order By: Relevance
“…Importantly, inactivation of CEBPD during cancer progression has been reported in breast cancer, cervical cancer, HCC, leukemia, and prostate cancer (16,39,40). In addition to the proapoptotic genes PPARG2 and GADD153 (41,42), our recent results suggested that CEBPD contributes to the transcriptional activation of procaspase-8 in prostate cancer (43). These observations further support the hypothesis that activation of CEBPD contributes to the induction of death signaling in cancer cells.…”
Section: Discussionsupporting
confidence: 73%
“…Importantly, inactivation of CEBPD during cancer progression has been reported in breast cancer, cervical cancer, HCC, leukemia, and prostate cancer (16,39,40). In addition to the proapoptotic genes PPARG2 and GADD153 (41,42), our recent results suggested that CEBPD contributes to the transcriptional activation of procaspase-8 in prostate cancer (43). These observations further support the hypothesis that activation of CEBPD contributes to the induction of death signaling in cancer cells.…”
Section: Discussionsupporting
confidence: 73%
“…Indeed, previous studies reported that 15dPGJ 2 can generate ROS in cancer cells (23,30), and ROS can induce CHOP production (31,32). To confirm this suggestion, we determined intracellular levels of ROS and calcium.…”
Section: Results 15dpgj 2 Sensitizes Trail-induced Cell Death In Hct1mentioning
confidence: 99%
“…Moreover, all stimulation of mRNA and protein expressions of CHOP and DR5 was almost completely abrogated by NAC (a ROS scavenger) but only partial reduced by BAPTA (a calcium chelator). In this aspect, previous studies showed that ROS is a molecular mediator inducing CHOP (31,32,46) and DR5 (10, 11, 47) expression.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that TG and ionophores induce transcriptional activation of Gadd153 by elevating [Ca 2ϩ ] i (35), and induction of Gadd153 may be required for release of cytochrome c from mitochondria and caspase activation (57). Gadd153 expression is also induced by oxidative stress (40 -42), and the age-related increase in Gadd153 expression is correlated with heightened sensitivity to oxidant injury (58). Increased Gadd153 expression also mediates dopaminergic death following intrastriatal injection of 6-hydroxydopamine (59), a hydroxylated dopamine analogue that is readily oxidized causing oxidant injury.…”
Section: Discussionmentioning
confidence: 99%